The Relationship between personal ethical ideology and perception of corporate social responsibility: an application in Turkey - Güler, Ahmet (My University, 2017)
Bu çalışmanın amacı bireysel ahlaki ideolojinin kurumsal sosyal sorumluluk algısı üzerindeki etkisini araştırmaktır. ABSTRACT The purpose of this research is to measure the effect of personal ethical ideology on the perception of corporate social responsibility.
Keywords: Bireysel Etik İdeoloji; Corporate Social Responsibility Perception; Ethics; Etik; İdeoloji; Kurumsal Sosyal Sorumluluk Algısı; Personal Ethical Ideology; Sosyal sorumluluk; Sosyal sorumluluk, Kurumsal